2007
DOI: 10.1186/1743-422x-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Different pH requirements are associated with divergent inhibitory effects of chloroquine on human and avian influenza A viruses

Abstract: Chloroquine is a 4-aminoquinoline previously used in malaria therapy and now becoming an emerging investigational antiviral drug due to its broad spectrum of antiviral activities. To explore whether the low pH-dependency of influenza A viruses might affect the antiviral effects of chloroquine at clinically achievable concentrations, we tested the antiviral effects of this drug on selected human and avian viruses belonging to different subtypes and displaying different pH requirements. Results showed a correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 30 publications
6
51
0
Order By: Relevance
“…In conclusion, we have found that although chloroquine is effective in vitro at limiting the replication of viruses expressing either an H1 or H3 HA in concurrence with other published reports, 7 , 8 this effect does not extend to in vivo models of influenza. At a concentration of 12.5 mg/kg/day we were not able to protect mice from significant weight loss following infection with either HK68 or PR8.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, we have found that although chloroquine is effective in vitro at limiting the replication of viruses expressing either an H1 or H3 HA in concurrence with other published reports, 7 , 8 this effect does not extend to in vivo models of influenza. At a concentration of 12.5 mg/kg/day we were not able to protect mice from significant weight loss following infection with either HK68 or PR8.…”
supporting
confidence: 91%
“…Recently, a series of in vitro studies have suggested that the antimalarial drug chloroquine may have activity against influenza and other emerging respiratory pathogens 6 , 7 , 8 , 9 . Chloroquine is a lysosomotropic agent that accumulates in the endosomal compartment where it can impair the acidification of the endosome and prevent the conformational changes associated with viral fusion and release into the cytosol.…”
mentioning
confidence: 99%
“…Preliminary studies have suggested that another viral strain, A/ISS PR/6/07 (H3N2), obtained from the Istituto Superiore di Sanità, Rome, Italy, a clinical isolate characterized by a mutation in the M2 gene that leads to a corresponding amino acid substitution at position 31 in the M2 protein associated with AMN resistance, is also susceptible to KP (data not shown). Furthermore, by using a recently described rapid test based on the inhibition of viral cytopathogenicity (8), KP was also shown to exert inhibitory activity on the replication of a H7N3 avian virus in vitro (A. Cassone and A. Savarino, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Proton carriers such as chloroquine are good inhibitors of the virus in vitro but lack efficacy in animal models and human trials. 42-44 However, by conducting electrophysiological assays in parallel with antiviral assays it is possible to eliminate many false positives from compounds that acted as proton carriers and delayed acidification of the endosome. We report here the first examples of compounds with specificity for both S31N and WT.…”
Section: Introductionmentioning
confidence: 99%